ANALISIS KEBIJAKAN PENDIDIKAN ISLAM DI TURKI: MODEL PENDIDIKAN TERPADU ANTARA TRADISI DAN MODERNITAS - Sanah, Nurhasanah (JURNAL AL-QAYYIMAH, 2024)
Islamic education has deep roots in the history of the Muslim community and plays a significant role in shaping cultural and social identities in various countries. Despite challenges such as stereotypes and discrimination, Islamic education in the diaspora continues to develop and adapt to local and global contexts. Through an in-depth analysis of various sources, including books, accredited national and international scholarly journals, documents on the education system and policies in Turkey, this research aims to understand the dynamics and challenges within the Turkish education system. The primary focus of this study is to evaluate the effectiveness of the curriculum, the role of technology in learning, and the impact of recent policies on educational quality. Additionally, the research will assess efforts towards social inclusion and the role of education in shaping students' character in the era of globalization. The findings reveal that Islamic education in Turkey has a strong religious foundation, beginning with the Ottoman Caliphate's establishment of madrasahs as centers for religious and scientific education. Significant changes also occurred in the Islamic education system and policies when the government transitioned to a Republic in Turkey.Keywords--Islamic Education, Integrity, Tradition-Modernity, Turkey.